PENGARUH PENGETAHUAN DAN SIKAP BIDAN TERHADAP INISIASI MENYUSUI DINI DI RSUD TENGKU RAFI’AN SIAK - Zuliyana Zuliyana (Ensiklopedia of Journal, 2020)
Early breastfeeding initiation (EBI) is a breastfeeding process that is done for 1 hour after the baby is born. Early breastfeeding initiation is important for baby survival and optimum growth because it can affect exclusive breastfeeding and can reduce infant mortality (IMR). The purpose of this study is to know the relationship of knowledge and attitude of midwife at Tengku Rafi'an Regional General Hospital, with population is 35 people type of research is an observational quantitative method with analytic design which is done in order to know the variables using cross sectional approach. The Sampling technique is this research is total sampling. the results of the study obtained a well-knowledge midwife of 20 people (57,1%), attitudes of midwife who agreed for 13 people (37,1%). The chi square test shows that there is a correlation between midwife knowledge (p=0,004), and midwife attitudes (p=0,001), to early breastfeeding initiation. The conclusion of this research is there is a correlation between knowledge and attitude of midwife to early breastfeeding initiation at Tengku Rafi'an Regional General Hospital 2017 with P-value < 0,05 therefore it is suggested to the midwife is expected to add an information about the importance of early breastfeeding initiation to increase the baby's life expectancy, in addition, it can be a midwife's motivation to implement early breastfeeding initiation.